Principles and Practicals in Medical Microbiology - Melter, Oto (Karolinum, 2014)
The book has been created for medical students to ease the comprehension of the relations between theory and practice in current medical microbiology. The core comprehensive data are reviewed from prestigious publications in the field and professional experience of the authors. Each chapter contains a theoretical and a practical part. The practical part is divided into a few exercises which allows for the practice of some of the basic experimental procedures used in laboratories of medical microbiology. We believe that the original photographs and the diagrams that have been newly created by the authors will improve the understanding of the basic principles of microbiological diagnosis. Each chapter is complemented with a lab quiz intended to help students review their basic knowledge.
Keywords: Ostatní lékařské obory